Case Report: Fatal cytomegalovirus pneumonia after CAR-T cell therapy in the long-term follow-up - Cheng, Jiali; Huang, Jin; Cao, Wenyue; Huang, Liang; Mao, Xia; Chen, Liting; Zhou, Jianfeng; Wang, Na (Frontiers in Immunology, 2023)
Introduction: The rapidly developed CAR-T cell therapy has a unique profile of side effects, which perhaps has not been totally realized and understood, especially the late-phase toxicity. CMV is prevalent world-wide and establishes a life-long latency infection. It can lead to life-threatening complications in immunocompromised host, and little is known about CMV disease in patients after CAR-T cell therapy. Here, we report a patient who developed possible CMV-pneumonia three months after anti-CD19 and anti-CD22 CAR-T cell therapy for relapsed B-ALL, contributing to the understanding of severe side-effects mediated by virus infection or reactivation in patients receiving CAR-T cell infusion. Case presentation: A 21-year old male patient with relapsed B-ALL received anti-CD19/22 CAR-T cell therapy, and achieved complete remission 2 weeks after the infusion. However, three months later, the patient was hospitalized again with a 10-day history of fever and cough and a 3-day history of palpitations and chest tightness. He was diagnosed with possible CMV pneumonia. Under treatment with antiviral medicine (ganciclovir/penciclovir), intravenous gamma globulin and methylprednisolone and the use of BiPAP ventilator, his symptoms improved, but after removing penciclovir his symptoms went out of control, and the patient died of respiratory failure 22 days after admission. Conclusions: CMV infection/reactivation can occur in patients long after receiving anti-CD19/22 CAR-T cell therapy, and induce fatal pneumonia, which reminds us of the late side effects associated with immunosuppression after CAR-T cell infusion.